A code of practice for grocery goods undertakings and an ombudsman: How to do a lot of harm by trying to do a little good - Paul K. Gorecki (The Economic and Social Research Institute (ESRI), 2009)
The Department of Enterprise, Trade and Employment in its August 2009 Consultation Paper, Code of Practice for Grocery Goods Undertakings, argues that a Code governing grocery supplier/retailer relations, enforced by an Ombudsman, should be introduced. The Code constrains the behaviour of the retailer with respect to certain practices that, for example, shift risk from the retailer to the supplier as well as those result in unexpected costs to suppliers. The rationale for the Code appears to be that due to the devaluation of sterling, combined with the recession, retailers are able to put increased pressure on local suppliers for lower prices, which in turn squeezes suppliers' margins. The paper argues that the Consultation Paper does not present a sound rationale for the Code, in reality the Code is a form of protectionism occasioned by the inflow of lower priced imports. Local suppliers should adapt through developing better products and becoming more efficient, rather than seeking shelter from market forces. The impact of the Code will likely be to lead to: higher consumer prices lowering consumer welfare and thus inconsistent with the declared aim of the Code; increased costs of doing business with local suppliers thus leading to an incentive for retailers to use more imports; and, perhaps, a less competitive grocery sector. It is argued that the Consultation Paper should be withdrawn and reissued, but in a manner consistent with the government's better regulation agenda which is currently ignored. To the extent that the issue of concern is excessive buyer power of retailers then that should be addressed directly: by liberalising the Retail Planning Guidelines as the Competition Authority has been arguing for sometime; and/or sponsoring entry of new retailers; and/or amending competition law, if a problem exists and can be demonstrated to exist, but retain the competition test. The answer, based on the evidence presented in the Consultation Paper, is not the Code.
Keywords: 330; better regulation; buyer power; countervailing buyer power; sterling devaluation; grocery products; imports; grocery code of practice; grocery ombudsman; Lebensmittelgroßhandel; Lieferanten-Kunden-Beziehung; Preisaufsicht; Schiedsgerichtsbarkeit; Irland